Testing for noninferiority of binomial distributions referring to a modified equivalence region with piecewise linear boundary - Wellek, Stefan (The journal of statistical computation and simulation, 2016)
In testing for noninferiority of two binomial distributions, the hypothesis formulation most commonly considered defines equivalence in terms of a constant bound to the difference of the two parameters. In order to avoid some basic logical difficulty entailed in this formulation we use an equivalence region whose boundary has fixed vertical distance from the diagonal for all values of the reference responder rate above some cutoff point and coincides left from this point with the line joining it with the origin. For the corresponding noninferiority hypothesis we derive and compare two different testing procedures. The first one is based on an objective Bayesian decision rule. The other one is obtained through combining the score tests for noninferiority with respect to the difference and the ratio of the two proportions, respectively, by means of the intersection-union principle. Both procedures are extensively studied by means of exact computational methods.
Gesehen am 01.07.2019
Published online: 10 Sep 2015